Mapping and characterization of a mutation in Escherichia coli that reduces the level of ribonuclease III specific for double-stranded ribonucleic acid - David Apirion; Ned Watson (1975)
Localization of a mutation affecting ribonuclease III activity (an enzyme specific for double-stranded ribonucleic acid) in Escherichia coli was attempted. By a series of matings and transduction experiments, the mutation rnc-105 was mapped near the nadB gene. In strains carrying this mutation, another mutation (ranA2074) was also found. Based on available data, their order on the E. coli chromosome appears to be tyrA, ranA, nadB, rnc, purI. Strains carrying either the ranA2074 or the rnc-105 mutation fail to grow at 45 C in enriched medium, whereas strains carrying only the rnc-105 mutation are defective in ribonuclease III activity. Strains carrying either of these mutations grow more slowly than corresponding wild-type strains in all media tested at all temperatures; the rnc-105 mutation reduces the growth rate more than the ranA2074 mutation. T4 and T7 bacteriophages form plaques with a lower efficiency on strains carrying the rnc-105 mutation than on other strains. Thus we suggest that ribonuclease III is beneficial for normal growth of E. Coli and that at higher temperatures it becomes indispensable.